Nanofiber-mediated gene silencing for directed stem cell differentiation - Low, Wei Ching (2015)
Stem cells hold great promise in facilitating the treatment of neural pathological conditions including trauma and degenerative diseases. However, the classical approach of generating neurons from stem cells, through bolus supplementation of small molecules or neurotrophic factors, is still lacking in the efficiency of neural conversion and lineage selection. Recent studies have highlighted the importance of biophysical and topographical cues from extracellular matrix (ECM) in modulating stem cell fate. Meanwhile, the novel technique of RNA interference (RNAi) has found increasing applications in the field of stem cell tissue engineering as a potential means for regulating stem cell proliferation and differentiation. Therefore, in this thesis, the synergistic effects of scaffold topographical cues and sustained delivery of drugs in the form of small molecules, neurotrophic factors and/or small-interfering RNAs (siRNA), was evaluated for its efficacy in enhancing stem cell neuronal differentiation. RE1-silencing transcription factor (REST), a negative regulator of many neuronal genes, was chosen as the RNAi target. Meanwhile, retinoic acid (RA) and brain-derived neurotrophic factors (BDNF) which play important roles in neurogenesis, were also included in this study. Preliminary two-dimensional (2D) study was first conducted to evaluate the feasibility of using REST siRNA to direct neural progenitor cells (NPCs) differentiation to neurons. Under both non-specific and neuronal induction conditions, REST silencing enhanced the kinetics of NPCs neuronal differentiation and the maturation of differentiated cells. Morphologically, a more robust development of neurite outgrowth from neuronal cells was also observed with REST knockdown. Thereafter, a scaffold-based drug delivery system was developed by electrospinning RA, BDNF and/or siRNA in a copolymer of ε-caprolactone and ethyl ethylene phosphate (PCLEEP). In this regard, the initial goal was to fabricate and establish a multifunctional, electrospun nanofibrous scaffold that is capable of delivering topographical and biochemical signals, along with gene silencing capabilities, for a sustained period of time to direct stem cell neuronal differentiation. Sustained release of RA and BDNF was achieved for at least 7 and 14 days respectively. Compared to bolus delivery, the nanofiber-mediated delivery of RA and/or BDNF induced comparable neuronal differentiation efficiency of the NPCs. Additionally, nanofiber topography significantly increased neuronal differentiation and reduced glial cell differentiation. Collectively, these results suggested that the synergistic effects of nanofiber topography and sustained drugs delivery may contribute towards the design of a multifunctional artificial stem cell niche for enhanced NPCs neuronal differentiation. Independently, siRNA-encapsulated PCLEEP nanofibers were also evaluated for long-term RNAi therapy. However, despite successful siRNA uptake into the cells, limited REST expression was observed. Furthermore, the direct encapsulation of siRNA in nanofibers faced restricted translatability to therapeutic implants due to potential compatibility issues that may exist between the harsh scaffold fabrication process and siRNAs integrity. As such, a simple, substrate-independent strategy that can incorporate siRNAs into any biomimetic tissue engineered scaffold was explored. Taking advantage of its intrinsic ability to deposit on a wide array of material surface and facile chemical reactivity towards biomolecules, the mussel-inspired polydopamine (PD) and DOPA-melanin (DM) coating was adapted for the functionalization of REST siRNA on polycaprolactone (PCL) nanofibers to enhance neuronal differentiation of NPCs and mesenchymal stem cells (MSCs) respectively. In general, sustained REST knockdown in both cell types was achieved with PD- and DM-mediated siRNA adsorption, and the knockdown efficiencies were significantly higher than on untreated PCL nanofibers. The silencing of REST, together with nanofiber topographical effect, significantly enhanced stem cell neuronal commitment while reducing astrocytic and oligodendrocytic differentiation. For cross-lineage differentiation of MSCs to neuronal cells, fiber alignment appeared to be a potent factor in promoting neuronal maturation of the differentiated cells as well. Taken together, these results demonstrated the potential application of bio-functionalized electrospun nanofibers for stem cell neural regenerative medicine. More importantly, nanofiber-mediated RNAi may serve as a promising alternative to achieve desirable stem cell differentiation outcomes for tissue engineering purposes.